Pengaruh Pemberian Kapur Dolomit dan Pupuk Urea terhadap Emisi Gas Karbon Dioksida (CO2) pada Tanaman Padi (Oryza sativa L.) di Tanah Gambut - Prayitno, Muh Bambang; Erlita, Lisa; Sulistyani, Dwi Probowati (Seminar Nasional Lahan Suboptimal, 2022)
Prayitno MB, Lisa E, Sulistyani DP.  2022. The effect of dolomite lime and urea fertilizer treatments on carbon dioxide (CO2) emissions in rice plants (Oryza sativa L.) on Peat Soil. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 234-242.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The study was conducted to determine the effect of treatment of dolomite lime and urea fertilizer on CO2 gas emissions in rice plants on peat soil. The research was carried out at the ATC Greenhouse, Faculty of Agriculture, Sriwijaya University, Indralaya, from March to June 2020.The research design was a Completely Randomized Factorial Design (RALF) with two factors, namely dolomite lime and urea fertilizer.Observations of gas emissions were carried out in various vegetative, generative and production phases. Gas capture is carried out with a closed chamber and then inserted into a vacuum tube. Carbon dioxide gas analysis was carried out in the laboratory of the Agricultural Environmental Research Institute, Ministry of Agriculture, Pati, Central Java. The results showed that the increase in urea fertilizer application decreased CO2 gas emissions at 30 DAP, 84 DAP and 100 DAP, but on the contrary there was an increase at 70 DAP. The lowest CO2 emissions in the vegetative, primordia, generative and production phases were U2D0, U2D2, U0D2 and U1D2, respectively.